2014
DOI: 10.1103/physreve.90.013025
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical interpretation of long-time tails of first-passage time distributions in porous media with stagnant parts

Abstract: Using a combined experimental-numerical approach, we study the first-passage time distributions (FPTD) of small particles in two-dimensional porous materials. The distributions in low-porosity structures show persistent long-time tails, which are independent of the Péclet number and therefore cannot be explained by the advectiondiffusion equation. Instead, our results suggest that these tails are caused by stagnant, i.e., quiescent areas where particles are trapped for some time. Comparison of measured FPTD wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Many of these studies involved no quenched disorder so that the system can be described as containing only particle-particle interactions. It is also possible for the particle motion to be stopped by some form of external constraints, such as flow through bottlenecks or funnels [12][13][14][15][16][17] , motion through a mesh [18][19][20][21][22] , flow over a disordered substrate [23][24][25] , or flow in porous media [26][27][28][29][30][31][32] . The particle flow stops when the combination of the particle density and the obstacle density is high enough.…”
mentioning
confidence: 99%
“…Many of these studies involved no quenched disorder so that the system can be described as containing only particle-particle interactions. It is also possible for the particle motion to be stopped by some form of external constraints, such as flow through bottlenecks or funnels [12][13][14][15][16][17] , motion through a mesh [18][19][20][21][22] , flow over a disordered substrate [23][24][25] , or flow in porous media [26][27][28][29][30][31][32] . The particle flow stops when the combination of the particle density and the obstacle density is high enough.…”
mentioning
confidence: 99%
“…At finite drive angles we observe a novel size-dependent clogging effect in which the smaller disks become completely jammed while a portion of the larger disks continue to flow. This work is relevant for filtration processes [14][15][16] , the flow of discrete particles in porous media 17,18 , and the flow and separation of of colloids on periodic substrates [19][20][21][22] Model and Method-We consider a 2D square system of size L × L where L = 60 with periodic boundary conditions in the x and y-directions. The sample contains N l disks of diameter σ l = 0.7 and N s = N l disks of diameter σ s = 0.5, giving a size ratio of 1 : 1.4.…”
mentioning
confidence: 99%
“…In contrast to periodic structures, random porous media typically also possess stagnant parts where the flow almost vanishes. Such stagnant parts are known to strongly influence the particle transport and dispersion [37][38][39]. Moreover, it has been observed that stagnant parts lead to the formation of vortices in viscoelastic fluids [40].…”
mentioning
confidence: 99%